Perancangan Aplikasi Kasir Berbasis Website Pada Toko Sembako Menggunakan Metode Waterfall - Muhamad Zein Akbar; Muhammad Afrizal Nur; Muhammad Fauzan Sabana; Thoyyibah Tanjung (CV. Multi Kreasi Media, 2022)
This research activity was carried out because the grocery store checkout was still done manually when entering data, so there was a queue of customers. The manual transaction system has many disadvantages, including recording transactions and searching for difficult data because every time you search for seller information, you have to record it with a large enough book. There is no information available to inform the amount of inventory, so it is not uncommon for store owners to know when the transaction process experiences problems that make customers disappointed. Because there are these weaknesses, it is necessary to have a web-based cashier application that can facilitate the management of data statistics carried out by the cashier waiter. The method used is waterfall, in the production of cash registers begin the stages of analysis, application design, coding implementation, application testing, error evaluation and development.